KEEFEKTIFAN MODEL PEMBELAJARAN KOPERATIF TIPE STAD DALAM PEMBELAJARAN MEMBACA PEMAHAMAN - Bambang Riadi; Mulyanto Widodo; Karomani Karomani (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2013)
The aim of this research is to examine whether the implementation of STAD cooperative learning model is effective in improving students’ reading comprehension. This research uses a quasi-experimental design. The population and sample in this research is the seventh grade students of SMP Negeri 2 Tegineneng Pesawaran with VIIA as experimental class, while VIIB as control class. The data collecting technique in this research is done by using test consisting of pre-test and post-test. Moreover, the data analysis technique used is t-test technique. The result of this research shows that the study of reading comprehension by using STAD cooperative learning model is effective in improving students’ reading comprehension of the seventh grade students of SMP Negeri 2 Tegineneng Pesawaran. Based on t-test result of pre-test and post-test in experimental class shows that the price of tcount is higher than ttable (13,174 2,034) which  means that there is significant difference between before and after treatment.Kata kunci: keefektifan model kooperatif tipe STAD, membaca pemahaman, siswa kelas VII.